Irisin: A potential link between physical exercise and metabolism—An observational study in differently trained subjects, from elite athletes to sedentary people - Benedini, S.; Dozio, E.; Invernizzi, P. L.; Vianello, E.; Banfi, G.; Terruzzi, I.; Luzi, L.; Corsi Romanelli, M. M. (BioMed Research International, 2017)
We compared irisin levels among groups of differently trained healthy individuals to explore the role of irisin as a physiological linker between exercise and metabolic health. Irisin and biochemical parameters of glucose and lipid metabolism were assessed in 70 healthy volunteers stratified for sport performance level into four groups: () 20 elite athletes of national level, () 20 subelite athletes of local level, () 20 recreational athletes, and () 10 sedentary subjects. All biochemical parameters were within the ranges of normality. Fasting glucose, HOMA-IR, and total cholesterol levels were inversely related to the degree of physical activity. HbA1c was higher in elite athletes compared to all the other groups (). A U-shaped relation between free fatty acids and the degree of physical activity was observed. All groups showed similar plasma irisin levels. After correction for the degree of insulin resistance (irisin/HOMA-IR), elite athletes showed higher levels compared to sedentary and recreational subjects ( and , resp.). In addition, the number of metabolic parameters correlated with irisin increased at increasing the training status. Our study suggests a correlation between sport performance, insulin sensitivity, and irisin levels. Irisin may be one potential mediator of the beneficial effects of exercise on metabolic profile.